CROSS-CULTURAL COMPONENT OF COPING STRATEGIES IN OLD AGE1 RELATIONS IN 1998-2008 - Afanas’yeva, Yulia; Gurieva, Svetlana (Revista Inclusiones, 2020)
The article describes cross-cultural peculiarities of coping behavior. It contains results of the study devoted to social and psychological peculiarities of men and women’s coping behavior depending on their ethnic background. We performed comparative analysis of social and psychological differences in coping behavior. Selection of the study included 160 persons, aged from 65 to 85 years, average age equals М=33.5, living in the Republic of North Ossetia – Alania of the Russian Federation. The following methods and procedures were used in the study: author’s questionnaire for determination of social and demographic characteristics of the respondents, “Coping Inventory for Stressful Situations” questionnaire (developed by N. Endler and J. Parker, adapted by T. Kryukova), COPE Questionnaire (developed by C. Carver, M. Scheier and J. Weintraub, adapted by T. Gordeeva, E. Osin, E. Rasskazova, O. Sychev, and V. Shevyakhova). The mathematical and statistical analysis of the obtained data included the following: Excel, “SPSS.13.0”, Student's t-test. As a result, we learned that there are significant differences in the coping strategies preferred by men and women, as well as by the respondents of different ethnic backgrounds. These results may be used for arrangement of social and psychological services in multi-cultural and multi-confessional regions, as well as for development of stress psychology, personality psychology, ethnic psychology and developmental psychology.